2019
DOI: 10.1038/s41598-019-42713-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of numerical aperture on quantitative use-wear studies and its implication on reproducibility

Abstract: Many archeologists are skeptical about the capabilities of use-wear analysis to infer on the function of archeological tools, mainly because the method is seen as subjective, not standardized and not reproducible. Quantitative methods in particular have been developed and applied to address these issues. However, the importance of equipment, acquisition and analysis settings remains underestimated. One of those settings, the numerical aperture of the objective, has the potential to be one of the major factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This approach has now reached a high degree of sophistication in the field, for both experimental and archeological samples (Stemp 2014). Since quantification methods have comparison and frames of reference as their main goals, researchers have realized that it is fundamental to define standards and protocols that improve data repeatability, reproducibility, and comparability (Adams 2014;Calandra et al 2019b;Dubreuil and Savage 2014;Evans et al 2014). This is of particular importance since different pieces of equipment are used by various researchers, and different settings can be applied during the analysis (Stemp et al 2013(Stemp et al , 2018.…”
Section: Nature and Subjective Description Of The Wear Tracesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has now reached a high degree of sophistication in the field, for both experimental and archeological samples (Stemp 2014). Since quantification methods have comparison and frames of reference as their main goals, researchers have realized that it is fundamental to define standards and protocols that improve data repeatability, reproducibility, and comparability (Adams 2014;Calandra et al 2019b;Dubreuil and Savage 2014;Evans et al 2014). This is of particular importance since different pieces of equipment are used by various researchers, and different settings can be applied during the analysis (Stemp et al 2013(Stemp et al , 2018.…”
Section: Nature and Subjective Description Of The Wear Tracesmentioning
confidence: 99%
“…Similar discussions have also taken place, for example, in dental microwear studies, where researchers have shown that dental microwear patterns correlate with diet. In archeological samples, the variation in wear patterns emphasizes the need for protocols, standardization, and quantitative methods when documenting and measuring surface textures (Calandra et al 2019b).…”
Section: Nature and Subjective Description Of The Wear Tracesmentioning
confidence: 99%
“…Our analyzed surfaces (sub-areas) are 50 x 50 μm, as in Evans et al [20]. The optical lateral resolution of the 50x/0.95 objective is high (see Supplementary Material 1 of [38] but the digital resolution (= pixel size) is too low (0.25 μm) to allow smaller areas to be analyzed. On the other hand, larger areas do not fit on the quartz grains of these quartzite varieties.…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, all data are fully accessible, and different surface analysis workflows and statistical comparisons will be possible with future research. Moreover, the full reproducibility of data acquisition is guaranteed by the reporting of the acquisition settings of the microscope used in this paper [37,38].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation